Insights into chitosan multiple functional properties: the role of chitosan conformation in the behavior of liposomal membrane. Issue 12 (4th September 2015) - Tan, Chen; Zhang, Yating; Abbas, Shabbar; Feng, Biao; Zhang, Xiaoming; Xia, Shuqin; Chang, Dawei
Abstract : Interactions of chitosan with liposomes correlate with multiple functionalities. Chitosan chains can self-aggregate above a critical aggregation concentration. The physical properties of liposomes are affected by chitosan conformation. Chitosan displays "polymeric surfactant property" in the form of coils. Abstract : Interactions between chitosan and the liposomal membrane are relevant to the physiological functionality of chitosan, including dietary fiber, antimicrobial action, and fabrication of a delivery system for bioactives. To elucidate the multiple functions of chitosan, the dependence of liposomal membrane properties on the biopolymer conformation was investigated. The concentration dependence of chitosan conformation in aqueous solution was quantified by fluorescence and viscosity measurements. As the concentration increased, the extended chains of chitosan (0–1.0 mg mL −1 ) partially crimped (1.0–1.5 mg mL −1 ), and then self-aggregated forming irregular coils (>1.5 mg mL −1 ). Adsorption of chitosan linear chains on the liposomal membrane surface tended to maintain the morphology of liposomes, decrease the membrane interior micropolarity and rigidify the liposomal membrane. However, these effects were negligible or even opposite in the case of chitosan coils. Analysis on the membrane fluidity revealed that the microviscosity of liposomes decorated by 1.5 mg mL −1 concentration of chitosan decreased by 17% after being heated at 80 °C for 10 min, in contrast to the decreased percentage of 55 at 4 mg mL −1 . Additionally, compared with the poor oxidative stability of liposomes decorated by chitosan coils, those decorated by chitosan linear chains exhibited slight lipid peroxidation with the TBARS inhibition of around 10% and 6% against oxygen and ferric ions, respectively. These findings suggest that the conformational effects of chitosan on the liposomal membrane are responsible for its multiple functional properties.